L’expérience agricole des citadins dans les jardins collectifs urbains : le cas de Montpellier - Pascale Scheromm (Développement Durable et Territoires)
Collective gardens, have multiplied in developed countries. In Montpellier city, their boost is due to the request of the citizens and supported by the municipality. Forty semi-structured interviews were conducted to investigate gardeners’ motivations, agricultural practices and view of gardening and farming. Reconnection of dwellers with farming was identified in these places with multiple functions, even if the objective of food production is not a priority. Our results suggest that this cultivated ordinary nature promoted by the city dwellers carries a new link between cities and agriculture.